The effect of silicon-based preparation on the amount of humus and essential nutrients in the soil - A, Mamasolieva M.; A, Gafurova L.; A, Jabbarov Z.; A, Hudoynazarov I. (Journal of Agriculture Sustainability and Environment, 2023)
In today's changing climate, increasing agricultural land use and soil productivity, as well as ensuring the availability of soil organic matter and soil essential nutrients, is becoming increasingly difficult. Farmers can increase crop yields by directly applying many commercial products and various pesticides to the soil, but this is only for this period. Due to the negative impact of such preparations on the basic properties of the soil, they can lead to the destruction of the soil structure in subsequent years. For long-term use of soil, it is very important that the fertilizers or preparations used are environmentally friendly and scientifically based. Today, to improve the relationship between soil and plant, many silicon-containing preparations are processed into the soil. This study examined the effect of silicon-containing Aminosid-Si and other Aminosid-Aton, Bionitrogen preparations on the amount of humus in the soil, the total content of N, P, K and N-NH4, N-NH3, P2O5 and K2O has been studied. Studies have been conducted comparing the effects of silicon-containing preparations with the effects of other preparations. Because of the study, positive results were recorded for the preparation of Aminosid-Si.